Unravelling the historical debates about Operation Coldstore : a historiographical study - Wee, Maurice Tian Ler (2018)
This historiographical paper examines the reasons for the polarized historiography of Operation Coldstore. As historians remain intensely divided over the basis of the covert operation, this paper argues that the conflicting historiography of Coldstore unfolds as a false dichotomy that presents readers with a false dilemma. This binary opposition inadvertently forces readers to take sides in the study of a complex episode in Singapore’s history. In a bid to illuminate the stifling historiographical effects of this dichotomy, this essay attempts to unravel the historical debates by systematically interrogating the false dichotomy. In doing so, the author aims to shed light on the persistent history war that plagues participants and stakeholders in the debates. This paper uses a wide range of sources such as archival documents, oral interviews, newspaper articles, as well as autobiographical works. This essay also cites extensively from scholarly literatures in the form of books and research articles. In addition, it selectively employs expository videos, podcasts and journalistic articles from independent online media platforms as sources in this discussion. Stepping away from the historiographical entanglement, this essay transcends mainstream historical debates and bridges a gap in the studies of Operation Coldstore.